Real-time gene analysis based on a portable electrochemical microfluidic system - Yichen Liu; Baiyang Lu; Yidan Tang; Yan Du; Bingling Li (Electrochemistry Communications, 2020)
Isothermal amplification, such as loop-mediated nucleic acid isothermal amplification (LAMP), is a highly promising technique that could revolutionize portable or point-of-care gene detection. However, the commonly used readouts of these isothermal reactions have been limited to a small number of options such as real-time fluorescence and colorimetric paper strips, which suffer from practical difficulties in further integration and quantitation, respectively. To enrich the readout library and provide more options suitable for a variety of detection requirements, we report a ready-to-use gene testing method based on the execution of isothermal nucleic acid amplification reactions on closed and portable PGE-LAMP electrochemical chips. Taking the HF183 gene of the fecal pollutant Bacteroides as a model target, this method allows both end-point and real-time transduction from genomic information to electrochemical signals with ultra-high sensitivity, specificity and a good signal-to-noise ratio, and with a detection limit as low as 80 copies. This approach is therefore highly promising for the development of point-of-care detection systems and accelerating the practical application of LAMP. Keywords: Electrochemical detection, Microfluidic chip, Isothermal amplification, Genetic detection